Adherence to the WHO Guidelines on Suicide Reporting: A Content Analysis from Bengaluru, India - Lekshmi Vimala; Bharath Rathinam; Gurucharan B Mendon; Ashok Kumar Bakka; Akanksha Rani; R. Dhanasekara Pandian; Santosh Loganathan; Richard Rego; Anish V. Cherian (Indian Journal of Social Psychiatry)
Background: Media, with its power to influence the masses, is found to have an impact on how the readers perceive suicide, and evidence suggest that suicidal behavior is contagious. However, studies have shown that it is possible to intervene by implementing media guidelines for suicide reporting. Unfortunately, the guidelines are mostly not being adhered to by the media. The current study attempts to assess if there has been any change in reporting after the Press Council of India issued guidelines on suicide reporting in 2019. Methodology: Content analysis of the newspaper articles reporting on suicide was done for 3 months (October 1, 2019, to December 31, 2019). Nineteen newspapers published in Bengaluru, Karnataka, were selected for the study based on the language and readership. These included six English, five Kannada, two Malayalam, two Hindi, two Tamil, and two Telugu newspapers. A total of 1198 reports were found and analyzed. Results: The study found that the majority of the reports did not adhere to the guidelines. It was observed that the news reports on suicide mostly resorted to sensationalization. Majority of the reports portrayed suicide in a harmful manner by mentioning the suicide method and the site in detail and focused on monocausal explanations. The significant connection between suicide and mental illness was also overlooked. Conclusion: Irresponsible reporting of suicide creates risks for the public and collaborative efforts should be designed to decrease the negative impact media can have on suicide prevention initiatives.